Significant risk factors affecting construction projects in Yemen - Hakami, Waled G. (Umm Al-Qura University, 2021)
Yemens construction industry faces many risks unknown to its players. This study aimed to identify the significant factors that affect construction projects in Yemen. A study used both qualitative and quantitative methods to enhance the study findings. Thus, 82 factors were extracted and categorized into 16 groups, which were the basis of questionnaire design. The study confirmed tools reliability and validity after the removal of group 16 of the tool. The relative importance index (RII) analysed the data according to their importance. The studys findings determined 10 significant factors affecting the construction industry in Yemen, such the contractors financial difficulties, currency exchange rate, and price changes (material & energy). This study recommends selecting contractors in light of their financial and technical capabilities, enacting laws granting professional grades to engineers, and activating the authorized training.